2015
DOI: 10.1111/plb.12403
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling reveals temperature effects on the VOCs and flavonoids of different plant populations

Abstract: Temperature is one of the key factors in limiting the distribution of plants and controlling major metabolic processes. A series of simulated reciprocal transplant experiments were performed to investigate the effect of temperature on plant chemical composition. Polygonum minus of different lowland and highland origin were grown under a controlled environment with different temperature regimes to study the effects on secondary metabolites. We applied gas chromatography-mass spectrometry and liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
(66 reference statements)
1
35
0
Order By: Relevance
“…Another secondary metabolite biosynthetic protein, enone oxidoreductase is involved in the production of furaneol, an aromatic volatile compound found in fruit such as pineapple and strawberry (Eshghi, Jamali & Rowshan, 2014; Klein et al, 2007). P. minor has been shown to increase both flavonoid and volatile organic compounds upon high temperature treatment (Goh et al, 2016), and this study further implies that MeJA elicitation could also exhibit similar response.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Another secondary metabolite biosynthetic protein, enone oxidoreductase is involved in the production of furaneol, an aromatic volatile compound found in fruit such as pineapple and strawberry (Eshghi, Jamali & Rowshan, 2014; Klein et al, 2007). P. minor has been shown to increase both flavonoid and volatile organic compounds upon high temperature treatment (Goh et al, 2016), and this study further implies that MeJA elicitation could also exhibit similar response.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have reported antioxidant, antiviral, antimicrobial and anticancer activities in P. minor extracts (Vikram et al, 2014). Our previous results showed increase in P. minor leaf volatile metabolites under heat stress (Goh et al, 2016) and MeJA elicitation (Rahnamaie-Tajadod et al, 2017). Transcriptome profiling indicated the activation of defense genes involving phenylpropanoid pathway upon MeJA elicitation (Rahnamaie-Tajadod et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…Each sample was crushed and ground until fine powder before lyophilised for 48 h. Extraction from the dried powder was performed according to [5] with slight modifications. Dried powder samples (10 mg) were extracted with 200 µL of methanol:chloroform:water (3:1:1).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…High temperatures may increase emissions of volatile organic compounds, which react in the lower atmosphere (Goh et al . ), while particulate pollution may interfere directly with plant ability to regulate the balance of water loss and carbon acquisition (Burkhardt & Pariyar ).…”
mentioning
confidence: 99%
“…Positive feedbacks between plant responses to stress and physiological responses that may further accelerate climate change are also considered. High temperatures may increase emissions of volatile organic compounds, which react in the lower atmosphere (Goh et al 2016), while particulate pollution may interfere directly with plant ability to regulate the balance of water loss and carbon acquisition (Burkhardt & Pariyar 2016).…”
mentioning
confidence: 99%